2018
DOI: 10.1172/jci94601
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine in omnivorous diets induces an atherogenic gut microbial pathway in humans

Abstract: BACKGROUND. l-Carnitine, an abundant nutrient in red meat, accelerates atherosclerosis in mice via gut microbiotadependent formation of trimethylamine (TMA) and trimethylamine N-oxide (TMAO) via a multistep pathway involving an atherogenic intermediate, γ-butyrobetaine (γBB). The contribution of γBB in gut microbiota-dependent l-carnitine metabolism in humans is unknown. METHODS. Omnivores and vegans/vegetarians ingested deuterium-labeled l-carnitine (d 3-l-carnitine) or γBB (d 9-γBB), and both plasma metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
228
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(240 citation statements)
references
References 65 publications
5
228
2
5
Order By: Relevance
“…Metabolomic studies have found that the profile of microbial metabolites is altered in NAFLD, which is commonly considered a secondary outcome of the altered gut microbial profile . Nevertheless, a number of metabolites are produced by gut bacteria utilizing dietary nutrients as precursors, indicating that diet has an important impact on gut microbial metabolites, in addition to its capacity to remodel directly the microbial profile . Therefore, gut microbial metabolites may serve as mediators in the gut–liver axis, highlighting the involvement of host–diet–microbiota–metabolite interactions in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic studies have found that the profile of microbial metabolites is altered in NAFLD, which is commonly considered a secondary outcome of the altered gut microbial profile . Nevertheless, a number of metabolites are produced by gut bacteria utilizing dietary nutrients as precursors, indicating that diet has an important impact on gut microbial metabolites, in addition to its capacity to remodel directly the microbial profile . Therefore, gut microbial metabolites may serve as mediators in the gut–liver axis, highlighting the involvement of host–diet–microbiota–metabolite interactions in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…TMAO and a TMAO precursor, y-butyrobetaine, have been associated with atherosclerosis [97,109]. In addition to this, TMAO has been associated with major adverse cardiovascular events.…”
Section: Tmao and Atherosclerosismentioning
confidence: 99%
“…For example, primary intestinal organoids represent a particularly useful tool to study human epithelium–microbe interactions for several reasons, including: they can be generated directly from humans (with or without disease‐associated genetic polymorphisms); they can be genetically modified using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas technology; they recapitulate important epithelial cell lineages and physical features of the intestinal tract; and they can be seeded with microbes of interest . Another promising approach is to identify factors like metabolites that can impact a response of interest and work to identify the microbes that are responsible for their production . As knowledge of the key mechanisms of host–microbiota interactions are revealed, our accuracy in predicting immunomodulatory activity based on the genomic content of a strain or community should markedly improve.…”
Section: Of Mice and Menmentioning
confidence: 99%
“…93 Another promising approach is to identify factors like metabolites that can impact a response of interest and work to identify the microbes that are responsible for their production. 94,95 As knowledge of the key mechanisms of host-microbiota interactions are revealed, our accuracy in predicting immunomodulatory activity based on the genomic content of a strain or community should markedly improve.…”
Section: Iga-based Purificationmentioning
confidence: 99%